Gallstone migration out of circuit: A case report of an intestinal perforation from an ectopic gallstone - MSEDDI, Mohamed Ali; Mokhtar, Abdelmalek; Nouri, Takwa; Sassi, Karim; Ben Slima, Mohamed (Biomedicine & Healthcare Research, 2025)
Introduction: Entero-biliary fistula is a rare and difficult-to-diagnose complication of cholelithiasis. While spontaneous evacuation may occur with small stones, surgical intervention is required in most cases. This condition presents significant challenges for the surgeon, as complete clearance of the digestive tract, along with cholecystectomy, may be fraught with difficulty. In this case, we report an instance of intestinal perforation caused by a migrating gallstone. Case Presentation: An 80-year-old woman presented to our surgery department with abdominal pain. Several diagnostic modalities were employed to reach a definitive diagnosis. Abdominal ultrasound confirmed the diagnosis of acute cholecystitis. The patient underwent urgent surgery after brief resuscitation. During exploration of the abdominal cavity, a punctiform perforation of an intestinal loop was identified. Upon bidigital palpation, a mass was felt that rolled over the fingers. The patient underwent segmental resection, double stoma creation, and feeding jejunostomy. A 2 cm gallstone was expressed from the specimen. Discussion: One of the rare complications of cholelithiasis is the development of an entero-biliary fistula. Small bowel perforation caused by a migrating gallstone is considered uncommon. The surgical challenge lies in managing both the perforation and the causative fistula, as cholecystectomy itself can be risky. Thorough examination of the small intestine during surgery is crucial to check for any additional intraluminal stones. Conclusion: Despite its rare prevalence and atypical presentations, a high index of suspicion for entero-biliary fistula is essential, particularly in patients with risk factors. With prompt diagnosis and timely intervention, patients can successfully recover from this clinical condition.